2016
DOI: 10.2147/ott.s99839
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium is a target of modulation of apoptosis in MCF-7 cells in the presence of IgA adsorbed to polyethylene glycol

Abstract: PurposeClinical and epidemiological studies have indicated that breastfeeding has a protective effect on breast cancer risk. Protein-based drugs, including antibodies, are being developed to attain better forms of cancer therapy. Secretory IgA (SIgA) is the antibody class in human breast milk, and its activity can be linked to the protective effect of breastfeeding. The aim of this study was to investigate the effect of polyethylene glycol (PEG) microspheres with adsorbed SIgA on MCF-7 human breast cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
2
9
0
1
Order By: Relevance
“…In constrast, MET treatment induced if Ca 2+ upregulation in both MOs and co-culture systems. Our findings support simultaneous MO activation and the induction of apoptosis in breast cancer cells as suggested previously (59,62,63).…”
Section: Discussionsupporting
confidence: 92%
“…In constrast, MET treatment induced if Ca 2+ upregulation in both MOs and co-culture systems. Our findings support simultaneous MO activation and the induction of apoptosis in breast cancer cells as suggested previously (59,62,63).…”
Section: Discussionsupporting
confidence: 92%
“…Changes in intracellular Ca2 + release by human cells may result in cell damage and activation of cell death pathways [45], and the release of large amounts of intracellular Ca2 + has been associated with induction of apoptosis in human cells. [13,44,46]. In this work, independent of the phases of day, the highest levels of apoptosis were observed in cells in the presence of melatonin adsorbed to the PEG microsphere, and the most expressive apoptosis was observed in the co-cultures.…”
Section: Discussionsupporting
confidence: 48%
“…Cancer development and progression is characterized by dynamic changes in the expression and function of protein kinases [42] or their signaling pathways, which can lead to malignant transformation of breast cells [43]. Studies have reported that a modified release system with antibodies [44] or melatonin [13] are capable of activating the signaling pathways involving calcium intracellular mechanisms and of inducing apoptosis in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…if Ca 2+ is an important secondary messenger that regulates various cellular processes and signaling pathways including those related to cancer, such as apoptosis, proliferation and metastasis [ 67 , 68 ], and those involved in immune responses of MOs, including the production of cytokines and phagocytic activation [ 69 , 70 ]. We first observed that if Ca 2+ levels were reduced in co-culture of MOs with breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%